The Ascona Charter: A Desire for Transformation or A Moral Argument? - Fournier, Laurent Sébastien (Swiss Journal of Sociocultural Anthropology, 2025)
How can we not adhere to the values ​​proposed by the Ascona Charter? Has transforming anthropology in order to transform the world never been more urgent?